"How to teach social entrepreneurship to teacher-candidates through cultural promenades: the teacher-candidates' views". Issue 3 (4th May 2021) - Brinia, Vasiliki; Psoni, Paraskevi
ABSTRACT: The present study examines the effectiveness of cultural promenades as an interdisciplinary methodology to teaching social entrepreneurship to teacher-candidates, whose teaching specialty is economics, informatics or business administration. The methodology of the cultural promenade included field-research in Orchomenus in Boeotia, Greece organised by DIAZOMA NGO and the Teacher Education Program of Athens University of Economics and Business. This experience of the teacher-candidates is examined in the present research paper through qualitative research and in-depth interviews with 9 teacher-candidates. According to some main findings, interviewees were able to realise the neglected value of the site, how they can bridge the past with the present and how they can utilise the monuments that they visited, in order to help develop the area of Orchomenus in Boeotia in socio-economic terms. The present study is of great importance for policy-makers, as well as for teacher education programs and school teachers worldwide.